APLIKASI TEORI KONSTRUKTIVIS PADA AL-QUR'AN HADIS - Arham, Rijal; Marhamah; Djubaedi , Dedi (Journal of Islamic Education Studies, 2022)
This study describes the implementation of constructivist learning theory. This study was written based on the importance of a constructivist approach that requires active students. One way to achieve this is a constructivist approach. The research method used is field research. The results of this study conclude that the application of constructivist learning theory is applied, although in a simple way. Constructivism is a positive activity that allows students to build knowledge, find meaning in what they have learned, and relate it to their own experiences.